Equine Sporotrichosis and Iatrogenic Hypothyroidism - Boscarato, André Giarola; Alberton, Luiz Romulo; Komochena, Henrique Augusto Elerbrock dos Santos; Botelho, Emerson; Ribeiro, Rita de Cássia Lima; Orlandini, Carla Faria; Steiner, Denis (Acta Scientiae Veterinariae, 2016)
Background: Sporotrichosis is a subacute or chronic granulomatous fungal infection that affects the dermis and subcutaneous tissue. Its etiology is related to a complex of Sporothrix spp. species of worldwide distribution. Usually, sporotrichosis results from traumatic inoculation of Sporothrix spp. into the dermis, affecting humans and other mammals, but a greater number of cases have been reported in felines, a fact increasingly important in the zoonotic transmission of diseased animals to man. In horses, there may be multiple ulcerated wounds covered with scabs and slightly elevated plaques or nodules that occur along lymphatic chains in limbs and can be unique and located. Iodides are considered drugs of choice for the treatment of sporotrichosis in horses. The main side effect of prolonged use of these substances is iodism and thyroid dysfunction. The aim of this study was to report a clinical case of sporotrichosis in an equine treated in the state of Paraná, southern Brazil, which showed secondary iatrogenic hypothyroidism with prolonged use of sodium and potassium iodide. Case: A female, 3-year-old, Quarter Horse, with 400 kg of liveweight presented at clinical examination of the cutaneous tissue elevated lesions of nodular aspect, with 2 to 4 cm in diameter, absence of itching and some nodules presenting alopecia areas in the chest and abdominal region, and in the anterior, posterior and internal regions of the hindlimbs, featuring diffuse distribution of lesions. Biopsy was performed for histological examination of affected tissue and microbiological culture in the attempt to isolate the etiologic agent. Treatment consisted of the use of intravenous potassium iodide (KI) at a dose of 2 mg / kg for 2 weeks, followed by oral sodium iodide (NaI) at a dose of 5 mg / kg, 10 days later and 20 mg / kg for a period of 65 days, totaling 100 days of treatment, during which hepatic, renal and thyroid functions were evaluated. Discussion: In the case described, empiric treatment with dexamethasone carried by the owner might have triggered the diffuse presentation of the disease restricted to the skin, as glucocorticoids interfere with immunity. The histopathological analysis of skin fragments obtained by biopsy and prepared with H.E. staining found mononucleate inflammatory infiltrate with the presence of lymphocytes and macrophages in deep dermis and necrotic foci. No microbiological isolation of S. schenckii was possible. They were described as a common side effect of the prolonged use of iodinated compounds, iodism and thyroid dysfunction. There were no changes in renal function; however, there was an increase in serum levels of ALT, GGT and FA, featuring liver dysfunction. Thyroid gland dysfunction was observed due to the low levels of thyroid hormones found in the bloodstream, featuring hypothyroidism. The animal of the present case report did not show clinical signs associated with hypothyroidism, which required no specific treatment, since normalization occurs with the gradual decrease of the body iodine levels after removal of the source. It was conclude that, despite the diffuse characteristic of the disease in the animal of this report, it was possible to obtain the clinical cure of sporotrichosis. Therapy with sodium and potassium iodide proved to be effective, but caution is recommended in the use of these drugs, as secondary iatrogenic hypothyroidism and liver dysfunction were observed due to the prolonged period of the required treatment. Keywords: hypothyroidism, fungal infection, sodium iodide, Sporothrix spp.